Germination and sugar content alteration in maize grain caused by Fusarium contamination - Keszthelyi, Sándor; Kerepesi, Ildikó; Pál-Fám, Ferenc (Acta Agraria Debreceniensis, 2010)
Healthy and Fusarium affected ears were collected in Fészerlak, Somogy County at the end of vegetation cycle of maize (25-30 August). Each pattern contains 25-25 ears. We compared the samples on the basis of visual image of Fusarium affection. The ears were shelled and two 0,5 kg samples were formed: healthy and Fusarium contaminated. After surface sterilisation the uniform sized seeds were soaked in sterile distilled water for 24 hours and there were germinated for 7 days. The α-amylase activity was measured with Phadebas- α-amylase test. Seeds were extracted one by one three times under reflux using 10 cm3 boiling water for 15 minutes. During our investigation germinating activity was detected to measure glucose, fructose, sucrose content and α-amylase activity. In the first seven days of germination the highest values were detected in control seeds followed by the affected seeds. Our results clearly show that stress conditions applied altered not only the saccharide content but decreased their germinating activity as well in the case of maize grain.